2021
DOI: 10.1002/hep.31837
|View full text |Cite
|
Sign up to set email alerts
|

Black Patients Have Unequal Access to Listing for Liver Transplantation in the United States

Abstract: BaCKgRoUND aND aIMS:The Model for End-Stage Liver Disease score may have eliminated racial disparities on the waitlist for liver transplantation (LT), but disparities prior to waitlist placement have not been adequately quantified. We aimed to analyze differences in patients who are listed for LT, undergo transplantation, and die from end-stage liver disease (ESLD), stratified by state and race/ethnicity. appRoaCH aND ReSUltS: We analyzed two databases retrospectively, the Center for Disease Control Wide-rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 32 publications
3
69
0
Order By: Relevance
“…As recently reported by our group, the advantage of using the LDR is that it incorporates both listings for transplantation and mortality from ESLD into a single metric with a higher LDR suggesting more favorable listing rates relative to the number of liver disease deaths (as a measure of need). ( 25 ) In our analysis of the LDR, states that expanded Medicaid had improvements in the annual percent change of the LDR after expansion, whereas the 2 cohorts of states that did not expand Medicaid (either with lenient or restrictive coverage) failed to have improvements. Notably, the relative improvements seen in ESLD mortality rates and the LDR in the expansion states did not occur as a result of increased listings for LT. Rather, listings for LT tended to remain relatively steady or decrease during the entire study period in all cohorts.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As recently reported by our group, the advantage of using the LDR is that it incorporates both listings for transplantation and mortality from ESLD into a single metric with a higher LDR suggesting more favorable listing rates relative to the number of liver disease deaths (as a measure of need). ( 25 ) In our analysis of the LDR, states that expanded Medicaid had improvements in the annual percent change of the LDR after expansion, whereas the 2 cohorts of states that did not expand Medicaid (either with lenient or restrictive coverage) failed to have improvements. Notably, the relative improvements seen in ESLD mortality rates and the LDR in the expansion states did not occur as a result of increased listings for LT. Rather, listings for LT tended to remain relatively steady or decrease during the entire study period in all cohorts.…”
Section: Discussionmentioning
confidence: 78%
“…The LDR is a metric that was recently reported by our group and reflects access to transplantation—measuring how effectively states listed patients for LT relative to their mortality rate from ESLD. ( 25 ) That is, a higher LDR may reflect higher relative access to LT listing. LT listings and ESLD mortality data were derived from the UNOS STAR data set and CDC WONDER data set, respectively.…”
Section: Methodsmentioning
confidence: 99%
“… 11 , 28 , 31 Although the MELD score has eliminated disparities while on the LT WL, black patients are less likely to be referred for LT evaluation, are less likely to pursue care at an LT center, and have lower listing to death and transplant to death ratios. 25 , 29 , 32 Recent studies have also found a significant burden of COVID‐19 infection, as well as lack of access to care during COVID‐19, among racial and ethnic minorities and communities and children disproportionately affected by COVID‐19, structural racism, and poverty. 23 , 33 These groups may also be disproportionately impacted by essential personnel status during COVID‐19 23 , 34 , 35 and by general distrust of the healthcare system and delays in seeking care.…”
Section: Discussionmentioning
confidence: 99%
“…R ates of referral to liver transplant centers (LTCs) and accessibility to liver transplantation (LT) waiting lists are low, with reported data in the literature of 5% to 21% [1][2][3][4][5] and 4% to 40%, [6][7][8][9][10][11][12] respectively. The reasons for the suboptimal referral rates to LTCs, which are the main cause of reduced access to waiting lists, are many.…”
Section: Q9 Q10mentioning
confidence: 99%